Lithic tool kits: A Metronome of the evolution of the Magdalenian in southwest France (19, 000–14, 000 cal BP). (1st September 2016) - Langlais, Mathieu; Sécher, Anthony; Caux, Solène; Delvigne, Vincent; Gourc, Laura; Normand, Christian; Sánchez de la Torre, Marta
Abstract: Under the Magdatis project a new evolutionary model has been proposed for the Middle and Upper Magdalenian based on a review of several lithic assemblages from southwest France. The Lower Magdalenian is not addressed in this article. Single lithic assemblages and stratigraphic sequences have been compared according to several parameters: the origin of the siliceous raw materials, the interconnection between domestic tool production and hunting armatures, and the typo-technology of the microliths. Alongside the new techno-economic data, the geographical distribution of certain practices and particular artefacts in southwest France has led to a discussion of the cultural geography of the different phases of the Magdalenian between 19, 000 and 14, 000 cal BP. The Early Middle Magdalenian covers an extensive European cultural territory, demonstrating social interactions over vast distances both in the circulation of raw materials and in the distribution of certain morphotypes of lithic armament. The Late Middle Magdalenian appears to correspond to a phase of population contraction in which cultural emulation is observed among lithic tool kits in the socio-economic value placed on large blades. The Early Upper Magdalenian coincides with the renewed settlement of the north Aquitaine plains. Among the technological innovations observed is the development of lithic points on small blades, leading to a first geographical division of the southwest (Aquitaine Basin versus Pyrenees). Finally, the Late Upper Magdalenian confirms this evolution of lithic equipment with new developments in lithic armaments in parallel with some easing off of the technical constraints associated with blade production. This period thus coincides with the progressive dilution of Magdalenian norms. With these four phases of the Middle and Upper Magdalenian, it is possible to gain a clearer understanding of the sequence of technical and economic changes observed in an environment in recomposition. At the same time, population fluctuations over these five millennia can be associated with developing phenomena of regionalism, particularly in the southwest of France.